Profile of repeat victimisation within multi-agency referrals - Shorrock, Sarah (International review of victimology, 2020)
To help reduce victimisation, safeguarding practices in England and Wales are becoming more multi-agency, with Multi-Agency Safeguarding Hubs (MASH) being a contemporary example of such an approach. MASH aims to reduce victimisation by identifying and managing vulnerability at the earliest opportunity. This is achieved through the co-location of safeguarding agencies, joint decision making and the co-ordination of interventions. Previous research has indicated that the demand placed upon MASH often outweighs available resources, questioning the extent to which MASH effectively safeguards vulnerable people at the earliest opportunity. Whilst existing literature has focused upon the characteristics of MASH referrals, alongside referral processes, rates of repeat referrals have been overlooked. This paper aims to bridge this gap by exploring the number of repeat referrals made over a two-month period to a MASH location in the north-west of England (n = 2,134). By investigating repeat referrals, reasons why some individuals are susceptible to being victimised on multiple occasions are identified. The paper concludes that whilst MASH has taken a step towards identifying and managing victimisation, practices and processes need to be reviewed if MASH is to proactively prevent repeat victimisation.